Analisis Strategi Pemasaran Digital Dalam Meningkatkan Loyalitas Pelanggan Pada Bisnis E-Commerce - Fatmawati Nasution (CV. SINAR HOWUHOWU, 2026)
The rapid advancement of digital technology has accelerated the growth of e-commerce businesses, creating increasingly competitive market conditions. In this environment, companies are required to implement effective digital marketing strategies to retain customers and enhance their loyalty. This study aims to analyze the effect of digital marketing strategies on customer loyalty in e-commerce businesses. The research employed a quantitative approach using descriptive and associative methods. Data were collected through questionnaires distributed to 150 respondents who were active users of e-commerce platforms. Data analysis techniques included validity testing, reliability testing, descriptive analysis, and simple linear regression analysis. The results indicate that digital marketing strategies were categorized as high, with an average score of 4.18, while customer loyalty obtained an average score of 4.05. Regression analysis revealed that digital marketing strategies have a positive and significant effect on customer loyalty, with a regression coefficient of 0.683 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) was 0.547, indicating that 54.7% of customer loyalty can be explained by digital marketing strategies. The study concludes that effective digital marketing strategies can significantly improve customer loyalty in e-commerce businesses through enhanced customer engagement, satisfaction, and overall customer experience.